2013
DOI: 10.1093/infdis/jit366
|View full text |Cite
|
Sign up to set email alerts
|

Placental Malaria and the Risk of Malaria in Infants in a High Malaria Transmission Area in Ghana: A Prospective Cohort Study

Abstract: There was no suggestion that exposure to PM directly increased incidence of malaria among infants of multigravidae. In our study area, absence of placental malaria in primigravidae is a marker of low exposure, and this probably explains the lower incidence of malaria-related outcomes among infants of PM-negative primigravidae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 27 publications
2
77
0
1
Order By: Relevance
“…However, as reported from the Kintampo Birth Cohort Study conducted in 2010, ITN use among women in the study area was low, 47% [19]. In a previous study conducted in Nigeria in 2012 [20], knowledge about the usefulness of ITNs in preventing malaria and the risk of malaria in pregnancy was concluded as the most likely factor required to increase ITN use.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, as reported from the Kintampo Birth Cohort Study conducted in 2010, ITN use among women in the study area was low, 47% [19]. In a previous study conducted in Nigeria in 2012 [20], knowledge about the usefulness of ITNs in preventing malaria and the risk of malaria in pregnancy was concluded as the most likely factor required to increase ITN use.…”
Section: Discussionmentioning
confidence: 92%
“…Malaria parasite prevalence among children below 5 years of age in the study area was about 50% in 2009 and the entomological inoculation rate was about 269 infective bites per person per year [18]. A birth cohort study conducted in 2010 in the study area showed that the prevalence of placental malaria was about 40% [19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Not at last, MiPexposure is associated with an increased risk of malaria during infancy, 38 which is partly attributed to familial socioeconomic status. 39 Still, cumulative effects of early-life exposure to malaria on the metabolic health in adult age are conceivable.…”
Section: Direct Effects Of Exposure To Mip On Metabolic Traitsmentioning
confidence: 99%
“…Malaria and respiratory infections are among the top ten diseases reported at health facilities(KNMA, 2013). There is significant poor ill-health among new-borns and infants; low birth weight prevalence is about 10% (Asante et al, 2013), neonatal mortality is 32/1000 live-birth, and infant mortality is 64/1000 child years (Kirkwood et al, 2010a). Health care is basic in the study area and the first point of call for an acute illness is a local chemical shop (Asante et al, 2010).…”
Section: Study Areamentioning
confidence: 99%